Pay a lot to a few instead of a bit to all! Evidence from online donation experiments - Yohei Mitani; Nobuyuki Hanaki (Osaka University, Institute of Social and Economic Research (ISER), 2025)
We conduct an online donation dictator game experiment with over 1,300 participants, representative of the Japanese population, to investigate the relationship between the incentive scheme and prosocial behavior by systematically varying the stake size and probability of being paid, including those where the expected payments are controlled. We find that stake size is the main driver of donation decisions, even in the hypothetical scenario. Our result suggests that paying a large amount to a few participants incentivizes donation decisions better than paying a small amount to many in large-scale online experiments.
Keywords: C91; D90; 330; Between-subject random incentive; Donation-dictator game; Social preferences